2012
DOI: 10.1134/s1070363212010100
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of organoalkoxysiloxanes by partial acidolysis of organoalkoxysilanes

Abstract: Partial polycondensation of RSi(OMe) 3 (R = C 6 H 5 , CH 3 ) by the reaction with АсOH in the presence of HCl is studied. Oligoorganomethoxysiloxanes are obtained of the average composition [RSi(OMe)O] 4 , [RSi (OMe) 4/6 O 7/6 ] 6 , RSi(OMe) 0.5 O 1.25 ] 8 , and [RSi(OMe) 0.4 O 1.3 ] 10 . Using the method of 29 Si NMR spectroscopy they were shown to contain three types of structural fragments: RSi(OMe) 2 O-, RSiOMe(O-) 2 , RSi(O-) 3 . Based on the kinetic data, on the composition, properties, and the 29 Si NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Under alternative conditions, such as omitting THF, resolution of the silanes can be readily achieved in the 29 Si dimension. 21 The in situ Raman spectra of the MTMS hydrolysis showed a remarkable similarity to that observed for the PTMS. All peaks are shifted to lower frequencies due to the change from phenyl to methyl group.…”
Section: Ab Initio Calculationsupporting
confidence: 52%
See 2 more Smart Citations
“…Under alternative conditions, such as omitting THF, resolution of the silanes can be readily achieved in the 29 Si dimension. 21 The in situ Raman spectra of the MTMS hydrolysis showed a remarkable similarity to that observed for the PTMS. All peaks are shifted to lower frequencies due to the change from phenyl to methyl group.…”
Section: Ab Initio Calculationsupporting
confidence: 52%
“…Under alternative conditions, such as omitting THF, resolution of the silanes can be readily achieved in the 29 Si dimension. 21
Figure 5.H–Si HMBC spectral series displayed right and 1 H NMR spectral series displayed left.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction has an induction period that could be substantially shortened by the addition of HCl or methanol. 10 These studies and related work by Muzafarov demonstrated that siloxane bond formation can be elicited by acidic transesterification processes. 11 As noted, the reaction is slow in the absence of strong acids.…”
Section: ■ Introductionmentioning
confidence: 89%
“…The reaction has an induction period that could be substantially shortened by the addition of HCl or methanol. 10…”
Section: Introductionmentioning
confidence: 99%